Effectiveness of a program to facilitate recovery for people with long‐term mental illness in Japan. (16th September 2013) - Chiba, Rie; Miyamoto, Yuki; Kawakami, Norito; Harada, Naoko
Abstract Recovery is defined as the process of developing new meaning and purpose in life as one grows beyond the catastrophic effects of mental illness. This study aimed to develop a program to facilitate recovery and examine its effectiveness in a randomized controlled trial. The program was developed with three components that enhance benefit finding, personal meaning, and a sense of happiness. Sixty‐three participants with long‐term mental illness were randomly allocated to the intervention group (n = 32) or the control group (n = 31). The intervention group attended eight 2‐h group sessions, with one held every week. Recovery was assessed at baseline, post‐intervention, and at a three‐month follow‐up. In the per‐protocol analysis, after excluding those who dropped out, the intervention group showed significant improvement in recovery compared with the control group (P < 0.05). In the intention‐to‐treat analysis, a repeated measures analysis of variance did not show any significant intervention effect (time × group) (P > 0.05). The program had the potential to facilitate recovery.